Simulasi Dispersi Emisi SO2, NOx, dan PM Pada Kegiatan Pertambangan Nikel Menggunakan Software AERMOD View - Muhammad Abdus Salam Jawwad; Muhammad Bagus Scheva Putra Mahendra (Prosiding ESEC, 2023)
Nickel mining activities have negative impacts on the environment, one of which is a decrease in air quality due to increased concentrations of air pollutants. Types of pollutants emitted from mining activities, including particulates, SO2, PM and NOx. Therefore, an air dispersion simulation is carried out to determine the maximum level of emissions released from the nickel mining process. This study uses a numerical modeling approach with Aermod View software to simulate the process of dispersion of SO2, PM and NOX air emissions in the distribution of emissions from nickel mining activities. Based on the simulation image of SO2 NOx gas dispersion, and particulates are scattered westward from the emission source/chimney following the wind direction. The dominant dispersion of SO2, NOx and particulates towards the west corresponds to the dominant wind direction. The highest SO2 concentration is around 22.57 x 10^-9 g/Nm3 which is located at a distance of approximately 100 meters from the emission source. The highest NOx concentration is 15.63 x 10^-9 g/Nm3 which is located at a distance of approximately 100 meters.